Human Resources Development In Increasing Employee Performance In (Case Study PT. Ars Indo Jaya Perkasa) - Susan Rachmawati; B Bilgah; Mety Titin Herawaty; A Asep; Nurul Aisyah; Arman Syah Putra (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
The background of this research is how to find out how to develop human resources in a company that aims to improve employee performance. Therefore, this research focuses on a company that wants to improve employee performance in order to improve the company so that it grows and develops. The method given in this study is to use a literature review and use a survey tool conducted on 100 employees, in a company. Therefore, the data obtained are real data. The problem raised in this study is how to find out what variables can affect the company's performance variables. Therefore, with a trial run with a survey, it can be seen what variables affect other variables so that it can be a suggestion for improvement in the company in this research. The purpose of this study is how to determine the development of human resources in a company in order to improve employee performance at PT. ARS INDO JAYA PERKASA the results of the research are several variables with human resources can improve employee performance in a company as an asset, the company will continue to grow in the future.